Gorlin Goltz Syndrome : A Review - M S Deepa; C Raphy Paul; Anita Balan (Wolters Kluwer Medknow Publications, 2003)
Gorlin syndrome is a rare autosomal dominant disorder characterized by multiple basal cell carcinomas, odontogenic keratocysts, tumors, and systemic anomalies. Early diac-iosis and treatment :s of utmost importance in reducing the severity of the long-term sequelae of this syndrome. and review of literature documenting both major and lesser-known manifestations of this disorder is given here.